U.S. North Pacific Surveying Expedition, Lieutenant John Rodgers, Commanding. Aleutian Archipelago, sheet no. 2 - United States North Pacific Exploring Expedition (1853-1856) (Washington, D.C. : United States North Pacific Exploring Expedition (1853-1856), 1855)
Relief shown by hachures and spot heights. Depths shown by soundings. Includes sailing directions, notes, 2 inset maps and 3 coastal views. Insets: Bay of Nazan -- S.w. part of Adakh Island. At head of title: U.S. North Pacific Surveying Expedition, Lieutenant John Rodgers, Commanding. Grayscale; 1:700,000